(3GdUdM GdhGbi ef GdGadGS (B: s (3OQGSI ebGQfI Hjf GdJTQjYjf GdchjJi hGdeUQi (B/ s - (3GSjd MGeO NdjaI GdaVGdIs; (3SejMI GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3JJdNU gPg GdQSGdI ai aUd JegjOi hKdGKI GHhGHhbO GTJedJ Ydi JejjR GdUdM GdhGbi ef GdGadGS ebGQfI HfXGe GdJShjI GdhOjI hGdJbhje GdbVGFi ai GdJTQjY GdJLGQi GdaQfSi (B: (3aVdG Yf JMOjO GdGSS GdJi jbhe YdjgG GdUdM GdhGbi ef GdGadGS ai GdJTQjYjf GdchjJi hGdeUQiabO JMOKJ GdQSGdI Yf GdTQhW GdehVhYjI hGdTcdjI ddUdM GdhGbi ef GdGadGS (B: (3Ke HjGf cjajI GfbVGA GdUdM GdhGbi ef GdGadGS (B: (3hGNjQG GdLQGFe GdJi JQJcH ai GWGQgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2006s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B567-581s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdGadGSs; (3GdUdM GdhGbi ef GdGadGSs; (3bGfhf GdJLGQI GdeUQis; (3GdJShjI GdhOjI s; (3TQhW GdUdM GdhGbj ef GdEadGS s; (3GdJbhje GdbVGFj s; (3GdJhba Yf GdOaY s; (3GdTQhW GdTcdjI ddUdM GdhGbj ef GdEadGS s; (3JbOje WdH s; (3GdhKGFb GdeQabI s; (3GfYbGO GdUdM GdhGbj s; (3GdbGfhf GdJLGQj GdeUQjs; (3GdJUOjbs; (3GdeOjfs; (3GdbGfhf GdJLGQj GdchjJj s; (3EHWGd GdUdM GdhGbj ef GdEadGSs; (3LQGFe GdUdM GdhGbj ef GdEadGSs; (3GdEadGS GdTNUj s; (3GdbGfhf GdaQfSj s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs